Pengaruh Akuntabilitas dan Transparansi terhadap Efektivitas Pengelolaan Dana Bantuan Operasional Penyelenggaraan di Lembaga PAUD - Elia Azizah; Arliyah Arliyah; Beti Nurasih; Fitri Wulandari; Puji Darwanti; Sisca Septiani; Wiwik Pudjaningsih (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Effective management of Operational Assistance (BOP) funds is a crucial factor in improving the quality of Early Childhood Education (PAUD) services. The BOP Fund has a strategic role in supporting the provision of facilities, infrastructure, and learning activities that are decent, equitable, and sustainable for early childhood. However, the effectiveness of its management is largely determined by the level of accountability and transparency of the organizing institution. This study aims to analyze the influence of accountability and transparency on the effectiveness of BOP fund management in PAUD institutions. The research method uses a quantitative approach with regression analysis techniques to test the relationship between variables. The research sample amounted to 40 respondents consisting of 15 school principals and 25 PAUD treasurers, selected by random sampling technique. Primary data were collected through a structured questionnaire based on a Likert scale of 1–5 that measured indicators of accountability, transparency, and effectiveness of the use of BOP funds. Data analysis includes classical assumption tests, reliability tests, t-tests, and linear regression analysis. The results of the study showed that there was a significant difference between the responses of the principal and the treasurer in the management of BOP funds with a significance value of 0.000 < 0.05. The regression analysis also confirms that both accountability and transparency have a positive and significant influence on the effectiveness of fund management. These findings confirm that accountable and transparent BOP fund management practices are able to improve the efficiency of fund use, strengthen stakeholder trust, create sound financial governance, and support the success of education programs in early childhood education.